Ragnar Nurkse (1907-2007) : classical development economics and its relevance for today - Kattel, Rainer, 1974-; Kregel, J. A.; Reinert, Erik S., 1949- (Anthem Other Canon series., 2009)
'Ragnar Nurkse (1907-2007): Classical Development Economics and its Relevance for Today' presents a selection of papers that casts new insight on Nurkse's thought, and discusses his relevance for today.